2014
DOI: 10.1016/j.envint.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Brominated flame retardant concentrations in sera from the Canadian Health Measures Survey (CHMS) from 2007 to 2009

Abstract: Pooling of surplus serum from individual samples, collected between 2007 and 2009 during Cycle 1 of the Canadian Health Measures Survey (CHMS), was performed to develop a national baseline estimate of brominated flame retardants in Canadians. Serum samples were categorized by sex and distributed by five age groups ranging from 6 to 79years. Nearly 5000 (4583) serum samples were used to form 59 composite pools. Serum pools were created to ensure a high detection frequency of these analytes in serum because low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 72 publications
5
22
0
Order By: Relevance
“…37 Rawn et al recently reported levels of BDE-153 in 59 pooled serum samples collected from 4583 individuals between 2007 and 2009 within the Canadian Health Measures Survey (CHMS). 27 The mean and geometric mean of BDE-153 levels in the 20–39 year old age group in CHMS were 12 ng g –1 lw and 11 ng g –1 lw, respectively. In comparison, the mean BDE-153 concentration observed in our study (18 ng g –1 lw) was higher, while the geometric mean (1.9 ng g –1 lw) was lower than that in CHMS.…”
Section: Discussionmentioning
confidence: 89%
“…37 Rawn et al recently reported levels of BDE-153 in 59 pooled serum samples collected from 4583 individuals between 2007 and 2009 within the Canadian Health Measures Survey (CHMS). 27 The mean and geometric mean of BDE-153 levels in the 20–39 year old age group in CHMS were 12 ng g –1 lw and 11 ng g –1 lw, respectively. In comparison, the mean BDE-153 concentration observed in our study (18 ng g –1 lw) was higher, while the geometric mean (1.9 ng g –1 lw) was lower than that in CHMS.…”
Section: Discussionmentioning
confidence: 89%
“…Although new production of commercial penta-and octa-BDE mixtures came under national and international control starting in 2003 and deca-BDE has also been slated for control (UNEP, 2010(UNEP, , 2013Environment Canada, 2013), PBDEs remain one of the most prevalent classes of flame retardant found indoors (Bradman et al, 2014;Abbasi et al, 2016 inter alia). Many studies have documented widespread human exposure to PBDEs and their putative health effects (e.g., Rawn et al, 2014;Eskenazi et al, 2013;Herbstman et al, 2010). Recently, Abdallah et al (2015) provided evidence for dermal absorption of PBDEs.…”
Section: Introductionmentioning
confidence: 98%
“…38,41 Statistical Analyses. Data normality was tested on raw or log transformed data using the Shapiro-Wilk test.…”
Section: ■ Introductionmentioning
confidence: 99%